ON THE APPROXIMATION OF FUNCTIONS OF THE HÖLDER CLASS BY TRIHARMONIC POISSON INTEGRALS - Kharkevych, Yurii I.; Zhyhallo, Kostiantyn M.; Харкевич, Юрій Іліодорович; Жигалло, Костянтин Миколайович (Ukrainian Mathematical Journal, 2001)
We determine the exact value of the upper bound for the deviation of the triharmonic Poisson integral from functions of the Hölder class.